Exploring the Longissimus Muscle: Unraveling its Correlation with Meat Quality in Bos indicus and Crossbred Bulls - Baldassini, Welder A. [UNESP]; Rodrigues, Rafaela C. [UNESP]; Magistri, Murilo S. [UNESP]; Machado Neto, Otavio R. [UNESP]; Torres, Rodrigo N. S. [UNESP]; Chardulo, Luis A. L. [UNESP] (MyJove, 2024)
This study investigated muscle tissue in Bos indicus and crossbred bulls to explain differences in meat quality traits. Carcass traits, meat quality parameters, and biochemical and molecular investigations of myofibrillar proteins are described. Methods for evaluating pH, intramuscular fat (IMF), meat color (L*, a*, b*), water losses, tenderness, and molecular biology assays have been outlined. Specific procedures detailing calibration, sample preparation, and data analysis for each method are described. These include techniques such as infrared spectroscopy for IMF content, objective tenderness assessment, and electrophoretic separation of MyHC isoforms. Color parameters were highlighted as potential tools for predicting beef tenderness, a crucial quality trait influencing consumer decisions. The study employed the Warner-Bratzler shear force (WBSF) method, revealing values of 4.68 and 4.23 kg for Nellore and Angus-Nellore (P < 0.01), respectively. Total cooking losses and biochemical analyses, including myofibril fragmentation index (MFI), provided insights into tenderness variations. Muscle fiber types, particularly myosin heavy chain (MyHC) isoforms, were investigated, with a notable absence of MyHC-IIb isoform in the studied Zebu animals. The relationship between MyHC-I and meat tenderness revealed divergent findings in the literature, highlighting the complexity of this association. Overall, the study provides comprehensive insights into the factors influencing meat quality in Bos indicus and crossbred (Bos taurus × Bos indicus) bulls, offering valuable information for the beef industry.